The Role of Inflammation after Surgery for Elders (RISE) study: Study design, procedures, and cohort profile. Issue 1 (1st December 2019) - Hshieh, Tammy T.; Vasunilashorn, Sarinnapha M.; D'Aquila, Madeline L.; Arnold, Steven E.; Dickerson, Bradford C.; Fong, Tamara G.; Jones, Richard N.; Marcantonio, Edward R.; Schmitt, Eva M.; Xu, Guoquan; Gou, Yun; Chen, Fan; et al.
Abstract: Introduction: The Role of Inflammation after Surgery for Elders study correlates novel inflammatory markers measured in blood, cerebrospinal fluid (CSF) assays, and [ 11 C]‐PBR28 positron‐emission tomography imaging. Methods: This study involved a prospective cohort design with patients who underwent elective hip and knee arthroplasty under spinal anesthesia. Sixty‐five adults participated with their family members. Inflammatory biomarker assays were measured preoperatively on day 1 and postoperatively at one month. Results: On average, participants were 75 years old, and 72% were female. 54% underwent total knee arthroplasty, and 46% underwent total hip arthroplasty. The mean Modified Mini‐Mental State (3MS) Examination score was 89.3; four patients (6%) scored ≤77 points. Plasma assays were completed in 63 (97%) participants, cerebrospinal fluid assays in 61 (94%), and PET imaging in 44 (68%). Discussion: This complex study presents an innovative effort to correlate peripheral and central inflammatory biomarkers before and after major surgery in older adults. Strengths include collecting concurrent blood, cerebrospinal fluid, and positron‐emission tomography with detailed clinical characterization of delirium, cognition, and functional status. Highlights: We describe the methodology of the Role of Inflammation after Surgery for Elders Study. This is a prospective cohort of elective hip/knee arthroplasty patients 70 years or older. We examine inflammation in blood, cerebrospinal fluid and positron emission tomography. We collect novel biomarkers preoperatively and one‐month postoperatively. There is clinical characterization of delirium, cognition and functional status.